Kepercayaan Organisasi dan Kesiapan terhadap Perubahan: Dampaknya terhadap Kinerja Karyawan melalui Job Crafting (Studi Empiris di PT Saudara Buana Samudera Medan) - Susanto Susanto; Hengky Kosasih; Wily Julitawaty; Syaifullah Syaifullah; Prianda Pebri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study analyzes the influence of organizational trust and readiness for change on employee performance directly and through job crafting mediation. This study was conducted at PT Saudara Buana Samudera Medan using a quantitative survey-based approach. The data were collected through questionnaires filled out by 78 permanent employees using the proportionate stratified random sampling technique. Path analysis was conducted using the SEM-PLS method. The results showed that organizational trust and readiness for change significantly affected employee performance. In addition, job crafting was a mediator that strengthened the relationship between these variables. This study provides theoretical contributions by integrating organizational trust, readiness for change, and job crafting to explain the mechanism of improving employee performance. Practically, these findings provide recommendations to the management of PT Saudara Buana Samudera Medan to build organizational trust and support job crafting to improve employee performance amidst organizational change. The study’s focus on a single organization necessitates caution when generalizing the results. Future studies can expand the sector’s scope or add moderating variables to enrich the findings. This study fills the literature gap regarding the role of job crafting in the relationship between organizational trust, readiness to change, and employee performance in the context of Indonesian companies.